An algorithm for managing adults who refuse medical treatment in New South Wales. (October 2018) - Cheng, Kylie; Wand, Anne; Ryan, Christopher; Callaghan, Sascha
Objectives: The assessment and management of a patient who refuses medical treatment requires clinical skill, and consideration of the relevant law and the patient's decision-making capacity. Psychiatrists are often asked to advise in these situations. We aimed to develop an algorithm describing the relevant legal pathways to assist clinicians, especially psychiatrists, working in New South Wales (NSW), Australia. Methods: We reviewed the academic literature on treatment refusal, relevant legislation, judicial rulings and NSW Health policy directives and guidelines. We consulted with clinicians and representatives of relevant tribunals. Results: We developed an algorithm for managing patients who refuse medical treatment in NSW. The algorithm emphases the evaluation of decision-making capacity and tracks separate pathways depending upon a person's status under the Mental Health Act 2007 (NSW). Conclusions: The algorithm provides a clear decision tree for clinicians responding to a patient refusing medical treatment in NSW.